A potentiometric biosensing system based on an isolated degrading bacterium Klebsiella sp. MP-6 for the determination of methyl parathion1. Issue 43 (14th May 2015) - Geng, Fangfang; Ding, Jiawang; Jia, Cuiying; Ding, Baojun; Qin, Wei
<x xml:space="preserve">Abstract</x> A potentiometric system for methyl parathion using bacterial cells as bioreceptors and an anion-sensitive electrode as a transducer is described.